SOCIALIZING THE MASS TRANSPORTATION PLANNING TO THE COMMUNITY IN WEST BANDUNG - Anwar, Rully; Rizal, Edwin (TEMALI : Jurnal Pembangunan Sosial, 2018)
This article discusses how public policies on transportation can be communicated to the community in West Bandung, West Java, Indonesia. It is important for the community because the development of transport services has a very close relationship with the social welfare and economic growth of a region. This can be demonstrated with an indication that the region has a complete transportation system works better than other regions, so that these regions tend to have better levels of social welfare and economic growth. Conversely, the less functioning transport would result in the emergence of social problems and environmental problems. The study here used a multiple case method. The cases consist of activities which is the implementation of the government’s program of socialization to the people of West Bandung on transportation. This regency is an expansion of Bandung regency; therefore, there are things that are new in government services, including the field of transportation. Interviews, observation and document analyses were used to collect the data. Face to face interviews using a list of questions were also developed for this study. The findings of the study indicate that in addition to its own designing and implementing transportation development plan in West Bandung regency itself, there is also a transportation development involving West Java provincial government, even the national government of Indonesia. All of the transportation plan could be properly communicated to the public because it uses a variety of media, both traditional and modern.